Nanogels as prospective Biomaterial: Radio-induced Synthesis, Characterization, and Biological Assays - Ges Naranjo, Adrian Alejandro; Viltres Cobas, Herlys; GarcÃa HernÃ¡ndez, Liudy; Ponce Rey, Liena; Aguilera Corrales, Yuri; Luz, Isabelle; Botelho, Katyelle; Fontes, Wagner (Revista Cubana de Investigaciones Biomédicas, 2021)
Nowadays, there is a growing interest in biodegradable polymers-based materials due to their diverse application in the biomedical field. Most studied systems involve biocompatible micro and nanodevices, such as liposomes, dendrimer, micelles or polymeric nanogels. The use of Radiation Technology, specifically gamma radiation, to produce micro and nanogels raises the possibility to obtain higher purity products, an important feature for biomedical and pharmaceutical applications. The radio-induced synthesis, characterization, cytotoxicity evaluation, and immunological response of nanogels are described in this study. Nanogel synthesis was performed in the absence of oxygen using aqueous polyvinylpyrrolidone solutions. Crosslinking reactions were carried out at 25 °C in a gamma irradiation chamber with a 60Co source. Nanogels properties were analysed by Scanning Electron Microscopy, Attenuated Total Reflection-Fourier Transform Spectroscopy, Dynamic Light Scattering, and Viscosimetry. The cytotoxicity and immunological response were evaluated by MTT test and analysis of the neutrophil respiratory burst. The results showed that nanogels formation strongly depends on the total absorbed dose. The nanogels have an elliptical shape and their chemical structure is similar to the initial polymer. The nanogels are biocompatible and promote a low-intensity neutrophil activation, similar to the well-characterized biomaterial TiO2, suggesting their potential biomedical uses.